The family of the priest. Structure of the household of the Castilian clergy in mid-18th century - Blanco Carrasco, José Pablo (Cuadernos de Historia Moderna, 2021)
Our knowledge of the residential structure during the Modern Age in Spain is, with lights and shadows, a subject on which there are numerous essays and papers. However, an important part of the population has not been studied in depth. We refer specifically to priests, chaplains, and other secular clerics, who were very common in towns and cities, and together with them to the whole family living under their tutelage and care.The aim of our work is to analyze this particular aspect of Early Modern society according to the typology of families and on the basis of the social history of the population.
Keywords: Secular Clerics; Family; Spain; 18th Century